INTERNATIONAL HISTOLOGICAL CLASSIFICATION OF TUMOURS OF DOMESTIC ANIMALS, Part 2 - (Διεθνής ιστολογική ταξινόμησις των όγκων των κατοικίδιων ζώων) Bulletin of the World Health Organization 1976, Vol. 53, No 2 - 3, 168 σελ. - Πάππους Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Δεν διατίθεται περίληψη.